Increasing Teacher Engagement in Learning Platforms through Future Workshops - Dirckinck-Holmfeld, Lone (Proceedings of the International Conference on Networked Learning, 2018)
The paper explores a methodical approach to implementation studies of learning platforms in Danish Schools, that combines Future Workshops (FWs), Activity Systems Analysis (ASA) and design interventions. The study documents a specific combination of approaches, new to the participatory design (PD) community, which provides ownership and creates meaning among participants in the implementation process. Further, the findings support that the meaning of using the platform is not given or determined, but is a negotiated enterprise under development in interaction with the plasticity of the platform and how the platform, principles and practices are combined with the teachers and the implementation process. The platform offers built-in design principles and pedagogical values and, as such, the materiality of the platforms afford certain practices. However, FWs, ASA and the design interventions also documented that the meaning construction is shaped under use (and no use). A critical and constructive appropriation of the learning platform is therefore strongly linked to participatory implementation methods in which teachers are exploring and experimenting with the learning platform in their professional practices. “The project will focus on creating coherence between the schools’ intentions and visions and the intentions behind the introduction of learning platforms (…) The project combines methodical approaches from Future Workshops, user involvement and design-based research, and will thus develop effective solutions that highlight and address problems and opportunities experienced in practice. At the same time, the project creates reliable and robust knowledge about how learning platforms affect teaching and learning in Danish primary school”. (Misfeldt, 2016 p. 2, my translation)